Karakteristik Bahasa Teks SMS Kolom “Lapor Cik” Harian Rakyat Bengkulu - Syaiful Abid (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to describe a precise, in-depth, and detailed understanding of, 1) the use of language in the SMS text of the